Geriatric patient outcomes in a multidisciplinary central nervous system community hospital clinic for radiation oncology and neurosurgery (RADIANS). Issue 5 (June 2022) - Gheewala, Rohi; Paez, Wencesley A.; Stadtlander, William; Lucke-Wold, Brandon; Jaboin, Jerry J.; Thomas, Jr., Charles R.; Mitin, Timur; Ciporen, Jeremy N.
Abstract: Introduction: Management of older adult patients with central nervous system (CNS) cancers requires a patient-centric, multidisciplinary approach. Assessment of neurosurgical and radiation treatment outcomes can assist in establishing guidelines for this patient population. We previously reported on the RADIANS clinic, a novel community hospital-based multidisciplinary clinic (MDC) for CNS cancer care, providing simultaneous radiation oncology and neurosurgery evaluation in a same-day, single-setting clinic. We now provide a focused analysis of our older adult patient population and recommendations for triage and standardization of care. Methods: Consecutive older adult patients (age ≥ 65) evaluated at the RADIANS clinic for CNS disease were identified and retrospectively reviewed. Observed 30-day neurosurgical outcomes were compared to predicted outcomes determined by the American College of Physicians NSQIP Surgical Risk Calculator. One-sample binomial exact tests were used to evaluate binary outcome measures. A two-sample t -test was used to evaluate the length of hospital stay. Brier Scores were calculated to assess the deviation between predicted probabilities and observed outcomes for binary outcome measures. Overall survival at 90 days was reported. Results: Fifty-six older adult patients with malignant (42/56) and benign (14/56) CNS disease were evaluated. Mean distance traveled for multidisciplinary evaluation at the RADIANS clinic was 43.4 miles. There was no incidence of radiation-induced toxicity. Mean length of hospital stay for RADIANS patients was significantly shorter by about 1.5 to 3.5 days (95% CI). There was no statistically significant difference for other outcome measures, however, Brier Scores demonstrated that NSQIP was not a good predictive tool for any or serious complications, UTI, venous thromboembolism, return to OR, readmission, or death in our cohort. Local tumor control rate and progression-free survival at 90 days were 97.4% and 76.9%, respectively. Conclusions: This is the first report of CNS disease outcomes in older adult patients evaluated by radiation oncology and neurosurgery at a community hospital-based MDC. We observed minimal adverse radiation outcomes and high tumor control in our cohort. Findings show significantly shorter postoperative hospital stay for patients evaluated and managed at the RADIANS clinic.